Influence of initial sulfur content in precursor solution for the growth of molybdenum disulfide - Tan, A. L.; Ng, S. S.; Hassan, H. Abu (2017)
This work investigated the influence of initial sulfur content in the precursor solution for the growth of molybdenum disulfide (MoS2) films by thermal vapour sulfurization (TVS) with sol-gel spin coating as pre-deposition technique. The early introduction of sulfur shows the presence of grains are uniformly distributed and homogeneous on the surface of the film. MoS2 (002) planes are detected for both films with and without initial sulfur conditions, however, the presence of initial sulfur contents gives slightly higher intensity of diffraction peak. Two phonon modes for MoS2, namely the E2g1 (in-plane) and the A1g (out-of plane), are well detected from which the frequency difference of Raman peaks between E2g1 and A1g suggest the grown MoS2 consisted of multi-layers. There is a slight shift of E2g1 which is caused by the carbon impurities but no shift for A1g. Besides, MoS2 film with the presence of initial sulfur content shows better crystal as indicated by its narrower Raman peaks linewidth. Two broad absorption peaks of MoS2 are detected at 614nm and 665nm. Hence, the early introduction of sulfur content in prepared precursor solution is one way of optimizing the growth of MoS2 films. disulfide (WS2), tantalum disulfide (TaS2), and Niobium disulfide (NbS2) [5,6]. MoS2 is one of the TMDs which has attracted significantly attention recently. Renewed interests in MoS2 are on its unique optical properties where the reduced dimensionality resulting in the transition from indirect (~1.2eV, bulk) to direct (~1.8eV, monolayer) bandgap, which is due to the quantum confinement effect [7]. Exfoliation method is the typical top-down method that is implied to cleave bulk MoS2 into monolayer or multi-layers of flakes [7]. The exfoliated MoS2 gives the good quality of free standing flakes, however, the inconsistency and non-uniform flakes size production has limited its application.